(untitled) (Journal of Hama University, 2025)
This research was conducted during the 2021/2022 agricultural season at Bouqa Farm in Lattakia to study the effect of cutting dates and seed rates on the productivity of green fodder and oat grains for dual-purpose use. The Syrian cultivated oat variety was used. Cutting was performed in two stages: at the tillering stage and then at the stem elongation stage, with a control treatment of no cutting. Three seed rates (100, 140, 180 kg/ha) were also tested. The experiment was executed using a randomized complete block design with three replications. The results showed a significant effect of cutting date and seed rate on the productivity and its components of the oat crop: The no-cutting treatment excelled in the number of tillers/m², the number of panicles/m², and the number of grains per panicle, which positively reflected on the grain yield, reaching (3211 kg/ha). The cutting treatment at the stem elongation stage achieved the highest green fodder yield, reaching (3283.6 kg/ha). Using a seed rate of 180 kg/ha showed a significant increase in grain yield, which reached (3191 kg/ha). The seed rates of 140 and 180 kg/ha recorded the best green fodder yields, reaching (3033.5 and 3246.3 kg/ha) respectively. The interaction between the no-cutting treatment and the 180 kg/ha seed rate achieved the highest grain yield, reaching (3686 kg/ha). Cutting the plants at the stem elongation stage with a 180 kg/ha seed rate led to the highest green fodder yield, reaching (3484 kg/ha).